2007
DOI: 10.1002/eji.200737103
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of NOD2 has a dual effect on proIL‐1β mRNA transcription and secretion of bioactive IL‐1β

Abstract: Synthesis and release of pro-inflammatory cytokines, such as IL-1b, play a crucial role in the intestinal inflammation that characterizes Crohn's disease. Mutations in the nucleotide oligomerization domain 2 (NOD2) gene are associated with an increased risk of Crohn's disease. Although it is known that NOD2 mediates cytokine responses to muramyl dipeptide (MDP), it is yet unclear whether NOD2 stimulation mediates only transcription of pro-IL-1b mRNA, or whether NOD2 is also involved in the activation of caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 42 publications
4
51
1
Order By: Relevance
“…Our results strongly suggest that, although NOD2 can signal to NF-B (11), its more critical function in the context of an actual bacterial infection is activation of caspase-1. This conclusion is consistent with a recent report that demonstrates that NOD2 plays dual roles in pro-IL-1␤ synthesis and caspase-1-dependent IL-1␤ maturation in human monocytes (30). Indeed, the absence of NOD2 prevents B. anthracis-induced IL-1␤ secretion but has little effect on pro-IL-1␤ synthesis in infected macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Our results strongly suggest that, although NOD2 can signal to NF-B (11), its more critical function in the context of an actual bacterial infection is activation of caspase-1. This conclusion is consistent with a recent report that demonstrates that NOD2 plays dual roles in pro-IL-1␤ synthesis and caspase-1-dependent IL-1␤ maturation in human monocytes (30). Indeed, the absence of NOD2 prevents B. anthracis-induced IL-1␤ secretion but has little effect on pro-IL-1␤ synthesis in infected macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a previous study (42), the simultaneous stimulation of different PRRs provides addictive effects, thus allowing the innate immune system to modulate the intensity of its response according to characteristics of the inflammatory trigger (virulence and amounts of the pathogens, variety, and relative abundance of DAMPs). The entire set of PRRs is likely redundant, with extensive cross-talk and possibly positive or negative feedback controls (3).…”
Section: Discussionsupporting
confidence: 90%
“…However, mammalian NOD2 was also shown to induce caspase-1 activation [44,45] but the present study found no effect of trout NOD2 on caspase-1 expression. Whilst further study is needed to determine whether fish NOD2 could activate caspase-1 at the post-translational level, it should also be noted that the role of caspase-1 in the fish inflammasome is less clear with no obvious ICE cute site present in IL-1b for example [28].…”
Section: Discussioncontrasting
confidence: 82%